Operator Inequalities of Morrey Spaces Associated with Karamata Regular Variation. (24th August 2017) - Wang, Jiajia; Fu, Zunwei; Shi, Shaoguang; Mi, Ling
Abstract : Karamata regular variation is a basic tool in stochastic process and the boundary blow-up problems for partial differential equations (PDEs). Morrey space is closely related to study of the regularity of solutions to elliptic PDEs. The aim of this paper is trying to bring together these two areas and this paper is intended as an attempt at motivating some further research on these areas. A version of Morrey space associated with Karamata regular variation is introduced. As application, some estimates of operators, especially one-sided operators, on these spaces are considered.